Handling the Rain Handler: Cultural and Religious Perspectives on the Indonesia’s Pawang Hujan - Wulan Kusumaningtyas (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to analyze the concept of the pawang hujan (rain handler) phenomenon and its connection with the culture and beliefs of the people in Indonesia. Through data collection and analysis from various sources within the last 10 (ten) years consisting of books, journals, and other relevant and supportive sources obtained through Google Scholar and the Google search engine, it is known that the people of Indonesia still believe in the effectiveness of the rain handler’s job. Although many people say that the rain handler deviates from religious rules, several others maintain the tradition of preserving Indonesian culture and local wisdom so that these cultural characteristics do not disappear over time. The responses were widely varied as one’s views wisely that belief in supernatural things must be gradually eroded for the religious people.